WORKING ON TRAUMA – A SYSTEMATIC REVIEW OF TF-CBT WORK WITH CHILD SURVIVORS OF SEXUAL ABUSE - Holtzhausen, Leon; Ross, Ashleigh; Perry, Rian (Social Work/Maatskaplike Werk, 2016)
Although there is growing interest in evidence-based practice (EBP), the implementation of research into clinical practice is still underutilised (DiCenso, Guyatt & Ciliska, 2005; Rycroft-Malone & Bucknall 2010). One emerging method in clinical practice with child survivors of sexual abuse is trauma-focused cognitive behavioural therapy (TF-CBT). This study aimed to systematically review the literature on TF-CBT work with child survivors of sexual abuse in an attempt to provide social work educators and practitioners with sufficient information about these treatments, which they can pursue in ongoing education and training